TECTONOPHYSICAL RESEARCH AT INSTITUTE OF THE EARTH’S CRUST SB RAS: MAJOR ACHIEVEMENTS AND ACTUAL PROBLEMS - Semen I. Sherman; Konstantin Zh. Seminsky (Геодинамика и тектонофизика, 2015)
The article presents major results which have been obtained during 30 years of researches conducted by the Laboratory of Tectonophysics at the Institute of the Earth’s Crust.General regularities in organization of fault-block structures in the brittle lithosphere are established. Relations between main parameters of faults are investigated, and their connection with the lithospheric structure and recent crustal movements is shown. A rheological model of vertical zoning of faults is proposed. Internal structures of faults are studied; stages in faulting are generally defined in terms of time; regularities of patterns of joints inside faults are described; and original methods of mapping such joints are proposed to reveal tectonic conditions of faulting.Based on seismic monitoring, new methods of quantitative assessment of relative activity rates of faults in real time are developed. Such methods are applied to delineate zones of recent destruction of the lithosphere in the Central Asian region. The state of stresses of the lithosphere is mapped, and the new map allows us to reveal regularities in the spatial mosaic of regions differing by types of stress fields.Our physical experiments conducted in compliance with similarity conditions are aimed at studying faulting mechanisms with regard to variable loads. A special set of experiments is devoted to the Baikal rift system. Cases of application of tectonophysical methods to study fault tectonics, the state of stresses and seismicity of the lithosphere are described. Prospects of tectonophysical researches conducted in the Laboratory and potentials of integration with studies of other research teams are considered.